Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/ijc.33373
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the incidence of cancer in Kampala, Uganda, 1991 to 2015

Abstract: Trends in the incidence of cancer in the population of Kyadondo County, Uganda—which comprises the city of Kampala and a peri‐urban hinterland—are presented for a period of 25 years (1991‐2015) based on data collected by the Kampala Cancer Registry. Incidence rates have risen overall—age‐adjusted rates are some 25% higher in 2011 to 2015 compared with 1991 to 1995. The biggest absolute increases have been in cancers of the prostate, breast and cervix, with rates of some 100% (prostate), 70% (breast) and 45% (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 31 publications
(45 reference statements)
1
28
1
Order By: Relevance
“…Cancer of the cervix uteri has been the most common cancer in Ugandan women since the 1950s 22. A previous study reported that the average increase in Kampala’s cervical cancer incidence rate was 1.5% over 25 years 3. We found that the burden of cervical cancer will remain high in the next decade.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Cancer of the cervix uteri has been the most common cancer in Ugandan women since the 1950s 22. A previous study reported that the average increase in Kampala’s cervical cancer incidence rate was 1.5% over 25 years 3. We found that the burden of cervical cancer will remain high in the next decade.…”
Section: Discussionmentioning
confidence: 53%
“…The global burden of cancer is predicted to rise to nearly 22 million cases and 13 million deaths by 2030, with the major burden on low/middle-income countries 2. Analysis from recent cancer surveillance data shows a gradual increase in the overall incidence of cancer in both sexes in Kampala, Uganda, with an overall increase in age-adjusted rates of 25% in the period of 2011–2015 compared with the period of 1991–1995 3. Even though the most commonly registered cancer over the 25-year period was Kaposi sarcoma (KS), these studies further suggested an increase in prostate, breast and cervical cancers in Uganda 3 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is rather a higher disease burden compared to that previously reported by Bukirwa et al where the disease incidence was found at 4.1%. 26 This difference in the statistics could be explained by the lack of nationwide screening programs and diagnostic capacities in regional referral hospitals. However, this seems to be a general problem for all LMICs where gaps in detection potentials are reflected in low incidences of CRCs and other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be due to a better health-seeking behaviour of Nigerian females in comparison to their male counterparts, and the relative vibrancy of obstetrics and gynecological unit in many Nigerian tertiary health institutions [22]. Some parts of the world with similar female preponderance of cancer include Ghana, Uganda, United States of America, while in China the reverse is the case [15,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%